Plukenetia volubilis leaves as source of anti-Helicobacter pylori agents - Aditya Tan; Katia Castanho Scortecci; Katia Castanho Scortecci; Katia Castanho Scortecci; Nathalia Maira Cabral De Medeiros; Wirginia Kukula-Koch; Thomas J. Butler; Sinéad Marian Smith; Fabio Boylan; Fabio Boylan (Frontiers Media S.A., 2024)
IntroductionHelicobacter pylori infection is a major issue worldwide, with widespread prevalence, combined with its link to gastritis, peptic ulcers, gastric cancer, and mucosa-associated lymphoid tissue (MALT) lymphoma. Meanwhile, effectiveness of current treatment protocols is limited by increasing antibiotic resistance and patient compliance issues due to long regimens and side effects. Plukenetia volubilis, or sacha inchi, is a valuable source of bioactive molecules. However, studies on its antimicrobial activity, especially against H. pylori, are lacking.MethodsIn this study, the anti-H. pylori activity of P. volubilis leaves water extract was explored using in vitro and in silico approaches. High-Performance Liquid Chromatography coupled to Electrospray Ionisation and Quadrupole Time-of-Flight Mass Spectrometry (HPLC-ESI- QTOF-MS-MS) analysis of the water extract from the leaves was used to characterise the chemical composition of the plant and allowed identification of some flavonoids, such as astragalin, and some phenolic compounds. Then, high-speed counter current chromatography (HSCCC) was used to fractionate the ethyl acetate partition obtained from the water extract from the leaves.Results and DiscussionThe presence of flavonoids derived from kaempferol was confirmed and astragalin was isolated for the first time in P. volubilis. The P. volubilis water infusion, ethyl acetate extract and the isolated astragalin exhibited anti-bacterial activity against H. pylori J99 and two clinical isolates (e.g., minimum inhibitory concentrations of 0.53, 0.51 and 0.49 μg/mL, respectively, for clarithromycin-resistant clinical isolate SSR366). Then, using molecular docking for potential protein targets for H. pylori, it was verified that astragalin could interact with these proteins by in silico analysis.ConclusionThese findings highlight that P. volubilis and astragalin produce a bacteriostatic activity against H. pylori and may have potential to be used in treatment against H. pylori, after further research.